The Contextual Parenting in the Digital Era: Parenting Strategies for Early Childhood Education toward a Golden Generation - Regina Aselia; Amanda Uli Orida; Achi Anggraini; Shela Ramadhan Putri; Fatrica Syafri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study develops a contextual parenting guide for children aged 0–4 years in the digital era. The development of a high-quality future generation largely depends on the quality of parental caregiving. However, formal education programs that prepare individuals for effective parenting remain limited. Society often focuses on fulfilling basic needs such as food, clothing, and shelter, while delegating academic education to schools and spiritual development to religious institutions. In reality, children's physical and mental well-being can only be ensured by adults who also maintain good physical and mental health, as well-being is a fundamental component of healthy development. One of the major concerns faced by parents today is protecting children from the negative impacts of digital technology while still enabling them to benefit from its advantages. Rapid social and technological changes require parents to raise children according to contemporary realities rather than relying solely on parenting approaches from previous generations. Family resilience serves as the foundation of national resilience, as the values cultivated within families contribute to the development of an ideal society grounded in national principles and values. In the contemporary context, the most valuable gift parents can provide is not material luxury but a high-quality educational environment at home. Children aged 0–4 years possess exceptional capacities for information processing, making early childhood an optimal period for fostering reading interests, communication skills, and positive developmental habits through guidance and meaningful dialogue. This article discusses practical approaches to addressing digital-era parenting challenges through question-and-answer sessions, applied recommendations, and case studies, including appropriate timing for smartphone introduction, strategies for managing gadget dependency, and the educational utilization of digital technology. The study concludes that there is no single universal parenting method. Successful parenting depends on consistency, an understanding of children's individual characteristics, and a commitment to raising children who are happy, loved, independent, and capable of understanding social norms.